Injury rate of soccer players and the efficacy of the FIFA 11 + Program - Saho, Y. (Sports injuries and prevention, 2015)
Soccer is the most popular sport in the world. There are more than 265 million soccer players worldwide (in 2006, http://www.fifa.com/worldfootball/bigcount/). In particular, youth and female players are increasing. In the 2008 Beijing Olympics and the 2012 London Olympics, soccer was categorized among the higher injury risk sports (Junge et al., Am J Sports Med 37(11):2165-2172, 2009; Engebretsen et al., Br J Sports Med 47(7):407-414, 2013). Injuries affect team performance negatively and exact high medical and social costs. In soccer, about 70 % of all injuries occur in the lower extremities (Dvorak et al., Br J Sports Med 45(8):626-630, 2011; Theron et al., Clin J Sport Med 23(5):379-383, 2013). The most commonly injured body parts are the thigh, ankle, lower leg and knee, and the most common types of acute injuries are contusions, ligament sprains, and muscle strains (Dvorak et al., Br J Sports Med 45(8):626-630, 2011; Theron et al., Clin J Sport Med 23(5):379-383, 2013; Dvorak et al., Br J Sports Med 41(9):578-581, 2007). Therefore a soccer-specific injury prevention plan was needed. The Federation Internationale de Football Association (FIFA) Medical and Research Center (F-MARC) developed "The 11" and then the "FIFA 11 +", soccer specific injury prevention programs designed to reduce soccer injuries and promote soccer as a health-enhancing leisure activity. In this chapter, the epidemiology of soccer injuries and the efficacy of the "The 11" and "FIFA 11 +" are covered.